Evaluating Investments in Information Technology - Del Carpio Gallegos, Javier Fernando (2000)
Investment in theinformation technology (IT) has been evaluated at different levels and with different approaches. This article aims to show laimportancia creating value through IT investment. however, it is convenient to consider the difficulties we may encounter in conducting our analysis, particularly when trying to estimate the intangible benefits.